2011
DOI: 10.1021/jf2030314
|View full text |Cite
|
Sign up to set email alerts
|

Chain Length Effects in Isoflavonoid Daidzein Alkoxy Derivatives as Antioxidants: A Quantum Mechanical Approach

Abstract: Daidzein, an isoflavonoid with known prooxidative effects in heterogeneous lipid/water systems, changes to an antioxidant for 7-n-alkoxy derivatives of daidzein. For an alkyl length increasing from 4 to 8, 12, and 16 carbons, the oxidation potential decreases gradually from 1.09 V (vs NHE) for daidzein (D) to 0.94 V for D16 in tetrahydrofuran as determined by cyclic voltammetry at 25 °C. The prooxidative effects transform into antioxidative effects from D8 with a maximal effect for D12 for aqueous phase initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 23 publications
(44 reference statements)
2
15
0
Order By: Relevance
“…An et al [129] Antioxidative and prooxidative properties are determined by internal factors (i.e., the oxidation substrates, structural organization and the microenvironment for the bioactive compound) and external factors (i.e., heat, pressure, and exposure to light). Hydrophobic alkyl chain increased water insolubility of 7-n-alkoxydaidzeins: daidzein, 7-n-butyloxy-daidzein, 7-n-octyloxy-daidzein, 7-n-dodecyloxy-daidzein, and 7-n-hexadecyloxydaidzein.…”
Section: Physical Structures Are Important Affectors Of Lipid Oxidationmentioning
confidence: 99%
“…An et al [129] Antioxidative and prooxidative properties are determined by internal factors (i.e., the oxidation substrates, structural organization and the microenvironment for the bioactive compound) and external factors (i.e., heat, pressure, and exposure to light). Hydrophobic alkyl chain increased water insolubility of 7-n-alkoxydaidzeins: daidzein, 7-n-butyloxy-daidzein, 7-n-octyloxy-daidzein, 7-n-dodecyloxy-daidzein, and 7-n-hexadecyloxydaidzein.…”
Section: Physical Structures Are Important Affectors Of Lipid Oxidationmentioning
confidence: 99%
“…Indeed, the effectiveness of antioxidants has been shown to increase as a function of increasing alkyl chain length until a threshold is reached for medium alkyl chain, beyond which any lengthening of the chain results in a collapse in this activity. This nonlinear effect, also known as a “cut‐off effect,” has been observed with various phenolipids (with saturated mono‐alkyl as lipophilic moiety) in several compartmentalized systems such as emulsions , liposomes , or living cells . These experiments showed that the lipophilic strength has to be finely tuned since a too low or too strong hydrophobic domain may result in a nonoptimal antioxidant activity.…”
Section: Resultsmentioning
confidence: 83%
“…Indeed, it was recently demonstrated that antioxidant activity increases as the hydrophobicity of the antioxidant rises until a threshold is reached for a medium lipophilic chain, beyond which any lengthening of the chain results in a collapse in this activity. This nonlinear effect, also known as a cut-off effect, has been observed with various phenolipids in oil-in-water emulsions [29][30][31][32][33], liposomes [34][35][36], and living cells [13,14,37,38]. In all of these studies, the lipophilic moiety was a saturated monoalkyl chain linked onto a carboxylic acid, an alcohol, or a phenolic hydroxyl from a phenolic antioxidant.…”
Section: Introductionmentioning
confidence: 89%